Aspek Pemanfaatan dan Pengembangan Tanaman Obat - Hidayat Moko (Pusat Penelitian dan Pengembangan Perkebunan, 1986)
The medicinal crops are natural resources that can support the development of medicinal materials technically and economically. They also take part in supporting the public health service. The medicinal crops are still used traditionally. The production hasn’t been supported by the valid research data. Accordingly it is necessary to plan and coordinate to improve these crops. The development of these crops is aimed at acquiring export commodities, supporting traditional and modern medicine industries and improving the germplasm collection, some of which tend to be vanished. It is important, therefore, that the research strategy and target be suttled in order to conduct research based on the terms which are agreed upon.